The protein phosphatase 2A B56γ regulatory subunit is required for heart development. Issue 6 (18th February 2014) - Varadkar, Prajakta; Despres, Daryl; Kraman, Matthew; Lozier, Julie; Phadke, Aditi; Nagaraju, Kanneboyina; Mccright, Brent
<x xml:space="preserve">Abstract</x> Background: Protein Phosphatase 2A (PP2A) function is controlled by regulatory subunits that modulate the activity of the catalytic subunit and direct the PP2A complex to specific intracellular locations. To study PP2A's role in signal transduction pathways that control growth and differentiation in vivo, a transgenic mouse lacking the B56γ regulatory subunit of PP2A was made. Results: Lack of PP2A activity specific to the PP2A‐B56γ holoenzyme, resulted in the formation of an incomplete ventricular septum and a decrease in the number of ventricular cardiomyocytes. During cardiac development, B56γ is expressed in the nucleus of α‐actinin‐positive cardiomyocytes that contain Z‐bands. The pattern of B56γ expression correlated with the cardiomyocyte apoptosis we observed in B56γ‐deficient mice during mid to late gestation. In addition to the cardiac phenotypes, mice lacking B56γ have a decrease in locomotive coordination and gripping strength, indicating that B56γ has a role in controlling PP2A activity required for efficient neuromuscular function. Conclusions: PP2A‐B56γ activity is required for efficient cardiomyocyte maturation and survival. The PP2A B56γ regulatory subunit controls PP2A substrate specificity in vivo in a manner that cannot be fully compensated for by other B56 subunits. Developmental Dynamics 243:778–790, 2014. © 2014 Wiley Periodicals, Inc.